Modelo de planejamento econômico como suporte ao planejamento estratégico pessoal - Frazzon, Lorenzo Sanfelice (2013)
Nowadays, the personal planning is a very important tool for individuals who seek a better quality of life, when planning the economic field becomes a large array of successful planning. For in addition to measuring personal success, supports the search for new goals, as well as enables ensure tranquility that reflects the financial well-being. In this context, the present study is to develop a Model of Economic Planning, to optimize the management of personal wealth, protecting and enhancing the heritage accumulated return on investment, according to the objectives, constraints and needs of the individual. The study was based on the model of Strategic Planning (ESTRADA, 2007), the model of Personal Planning (ESTRADA, 2011), the Modern Theory of Finance and Investment Management Models that address the key aspects for the development and maintenance s personal assets. The methodology consisted in a qualitative research with exploratory objective and descriptive. For the study design was used for literature review and survey. A description and critical analysis of the literature review allowed us to establish the essential elements for the development of the Model Economic Planning. The model consists of four steps that must be developed sequentially, the steps of the model are: Assessment, Formulation, Implementation and Monitoring, and their respective phases. It was also performed to evaluate the profile of the investor using the Item Response Theory (IRT), which proved to be possible calibrate the items to measure the degree of risk tolerance.